Contribution to understanding the color development on wood surfaces treated with iron salts by a combination of analytical methods. (3rd July 2020) - Dagher, Roberta; Landry, Véronic; Stevanovic, Tatjana
Abstract: Metal salts application on wood surface is a simple and nontoxic method that can be used for wood color modification, which is induced by the formation of colored complexes between wood extractives and metal ions. In this study, we have combined several analytical methods to understand the color development for four North American hardwood species: white oak, red oak, sugar maple and yellow birch. The phenolic composition of the ethanolic extracts of heartwood and sapwood of the four wood species was studied by UV-Vis spectrometry and liquid state phosphorus-31 nuclear magnetic resonance spectroscopy (31P NMR) and analyzed in relation to color development. The correlations between different OH types and the color development as measured with the CIEL*a*b* color coordinates, indicate that the descending order of correlation for phenolic hydroxyls was: di-substituted OH, mono-substituted OH and un-substituted OH while no correlation was found between COOH hydroxyls and total color change (ΔE).